Forensic classification of military criminal offences and the place of abuse of power or authority by a military official - I. Kostiuk (Юридичний часопис Національної академії внутрішніх справ)
The relevance of the study lies in the need to develop a forensic classification of military criminal offences, in particular, those related to abuse of power or authority by senior military personnel. This study aimed not only to improve the effectiveness of investigations, but also to provide legal protection for participants in military legal relations, which gives it significance in theoretical and practical contexts. The methodological approaches included comparative analysis, classification methods, and typology, which were used to divide military criminal offences into appropriate categories, types, and subtypes, considering their legal and forensic characteristics. As a result of the conducted research, several key conclusions were substantiated. Given the specifics of public relations in the military sphere, it was proposed to consider criminal offences against the established procedure for military service as a separate type of forensic classification. This type covers a wide sector of socially dangerous acts united by common generic features. Within the specified type, groups and forms of offences were identified, characterised by specific features depending on the object of illegal encroachment. When classifying the types of such offences, the emphasis was placed on a detailed structured form that reflects the specific features or conditions of committing a particular type of action. Highlighting the subtypes of criminal offences related to abuse of power or official authority by military personnel, attention was focused on the methods of their commission and socially dangerous consequences. This approach enabled a systematic study of the legal mechanism for committing military offences and their impact on the observance of discipline and the rule of law in the military environment. The results obtained contribute to improving the forensic classification of military criminal offences, which is important for their effective investigation and prevention